AUGMENTED REALITY (AR) IN RETAIL: AN ANALYSIS OF AR-DRIVEN APPLICATIONS ON CONSUMER PURCHASE INTENTION AND USER EXPERIENCE - Sun Wei; Jung Yuna; Lim Haeun (Journal of Social Entrepreneurship and Creative Technology, 2026)
The rapid growth of augmented reality (AR) technology has significantly transformed the retail landscape by providing innovative ways to enhance consumer experiences and influence purchasing decisions. As retail businesses increasingly incorporate AR applications, understanding their impact on consumer purchase intention and user experience is crucial. This study aims to analyze the role of AR-driven applications in retail and assess their influence on consumer behavior. The research employs a mixed-methods approach, combining a survey and semi-structured interviews to gather data from 300 retail consumers who have interacted with AR applications in both in-store and online settings. Quantitative data were analyzed using regression analysis to determine the relationship between AR features and purchase intention, while qualitative data were thematically analyzed to explore the user experience. The results indicate that AR applications with high interactivity and realism significantly increase consumer purchase intention and enhance user satisfaction. Moreover, user satisfaction was found to mediate the relationship between AR interactivity and purchase intention. This study highlights the transformative potential of AR in retail, providing actionable insights for retailers to optimize their AR offerings. The findings contribute to the growing body of knowledge on AR in retail and offer valuable guidance for integrating AR technology into retail strategies.